Improved gravity anomaly fields from retracked multimission satellite radar altimetry observations over the Persian Gulf and the Caspian Sea - Khaki, M.; Forootan, E.; Sharifi, M.; Awange, Joseph; Kuhn, M. (Oxford University Press, 2015)
Satellite radar altimetry observations are used to derive short wavelength gravity anomaly fields over the Persian Gulf and the Caspian Sea, where in situ and ship-borne gravity measurements have limited spatial coverage. In this study the retracking algorithm ‘Extrema Retracking’ (ExtR) was employed to improve sea surface height (SSH) measurements that are highly biased in the study regions due to land contaminations in the footprints of the satellite altimetry observations. ExtR was applied to the waveforms sampled by the five satellite radar altimetry missions: TOPEX/POSEIDON, JASON-1, JASON-2, GFO and ERS-1. Along-track slopes have been estimated from the improved SSH measurements and used in an iterative process to estimate deflections of the vertical, and subsequently, the desired gravity anomalies. The main steps of the gravity anomaly computations involve estimating improved SSH using the ExtR technique, computing deflections of the vertical from interpolated SSHs on a regular grid using a biharmonic spline interpolation and finally estimating gridded gravity anomalies. A remove–compute–restore algorithm, based on the fast Fourier transform, has been applied to convert deflections of the vertical into gravity anomalies. Finally, spline interpolation has been used to estimate regular gravity anomaly grids over the two study regions.Results were evaluated by comparing the estimated altimetry-derived gravity anomalies (with and without implementing the ExtR algorithm) with ship-borne free air gravity anomaly observations, and free air gravity anomalies from the Earth Gravitational Model 2008 (EGM2008). The comparison indicates a range of 3–5 mGal in the residuals, which were computed by taking the differences between the retracked altimetry-derived gravity anomaly and the ship-borne data. The comparison of retracked data with ship-borne data indicates a range in the root-mean-square-error (RMSE) between approximately 1.8 and 4.4 mGal and a bias between 0.4062 and 2.1413 mGal over different areas. Also a maximum RMSE of 4.4069 mGal, with a mean value of 0.7615 mGal was obtained in the residuals. An average improvement of 5.2746 mGal in the RMSE of the altimetry-derived gravity anomalies corresponding to 89.9 per cent was obtained after applying the ExtR post-processing.